2009
DOI: 10.1007/s10994-009-5161-3
|View full text |Cite
|
Sign up to set email alerts
|

A cooperative coevolutionary algorithm for instance selection for instance-based learning

Abstract: This paper presents a cooperative evolutionary approach for the problem of instance selection for instance based learning. The model presented takes advantage of one of the recent paradigms in the field of evolutionary computation: cooperative coevolution. This paradigm is based on a similar approach to the philosophy of divide and conquer. In our method, the training set is divided into several subsets that are searched independently. A population of global solutions relates the search in different subsets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 47 publications
0
22
0
1
Order By: Relevance
“…In García et al (2008), a memetic algorithm is proposed for instance selection, tackling the problem of selection in large scale databases. A cooperative coevolutionary algorithm is used for instance selection in García-Pedrajas et al (2010), where the obtained results compared favorably with standard and also recently published state-of-the-art algorithms (see Garcia et al (2012); Olvera-López et al (2010) for more details).…”
Section: Data Reduction Based On Evolutionary Algorithmsmentioning
confidence: 82%
“…In García et al (2008), a memetic algorithm is proposed for instance selection, tackling the problem of selection in large scale databases. A cooperative coevolutionary algorithm is used for instance selection in García-Pedrajas et al (2010), where the obtained results compared favorably with standard and also recently published state-of-the-art algorithms (see Garcia et al (2012); Olvera-López et al (2010) for more details).…”
Section: Data Reduction Based On Evolutionary Algorithmsmentioning
confidence: 82%
“…The idea is to decompose a high dimensional problem into a number of manageable, low dimensional problems for the purpose of solving the main problem. García et al (2010) used coevolution by decoupling the dimensions of a problem to form subpopulations. Li and Yao (2009) proposed a variant of cooperative coevolution.…”
Section: High Dimensionality Specific Easmentioning
confidence: 99%
“…With a population over the populations that evolved the subproblems, they try to account for the dependencies among the subcomponents. They applied that method to the evolution of neural networks [54], ensembles of classifiers [55], and instance selection [53]. In the coevolution of instance selection, they found that the method scaled better to large problems than monolithic evolutionary algorithms.…”
Section: Cooperative Approach In Evolutionary Computationmentioning
confidence: 99%